Desarrollo e implementación de un sistema de evaluación y capacitación enfocado al uso y manejo de equipos biomédicos para personal asistencial (2020)
The main objective of this project was to develop and implement a evaluation and training system about the correct use and management of biomedical equipment with the purpose of reduce the biomedical engineering calls in a hospital with second level of complexity. For this goal, a test was made to measure the knowledge perception about multiparameter monitor, defibrillator, electrocardiograph and mechanical fan. After the first evaluation a training was given for a ideal use of this devices. When this part is finished, a second test was offered to analyze the new knowledge. To compare this tests a Kolgomorov-Smirnov and Wilcoxon signed rank test were included. Finally a comparison between September and October calls was used. The principal result was the improving data after the first result and training furthermore the reduced calls.